DOCUMENTS REGULATING THE VOCATIONAL TRAINING OF MUSIC PERFORMERS IN LITHUANIA AND INTERNATIONALLY: DIRECTIONS, CHARACTERISTICS AND SHORTCOMINGS - Daucianskaite, Agne; Zydziunaite, Vilma (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Here is lack of clarity in documentation regarding music performers’ training in Lithuania and internationally. Here is lack of information and research-based knowledge regarding strategies, methods, philosophies, competencies and etc., regarding music performers’ training. So why it seems for society as “for granted” and that is based on personal talents that are heritage. Also here is lack of documents on requirements for teachers, who prepare the music performers. The aim of the study is to discuss the issue of music performers’ training and education regarding orientations, directions, characteristics and other peculiarities with the focus on a current training and education situation. The study is based on document analysis. Documents on musicians’ training, which exist in Lithuania and internationally, they lack precision, clarity, specificity in terms of specializations, instruments, levels of achievement(s), specifications for performance assessment, and levels of professionalism achieved. Most of the documents are generic, politicized, and their content is deliberative about how it must be, what shows that documents do not rely on empirical research evidence within the practical reality, and are not oriented to realistic ways, how to achieve the specific results that reflect the quality of musical performance.